Microvascular free flap reconstruction in head and neck cancer cases with vessel depleted necks and distorted anatomy due to prior intervention - Rajgor, Darshil K.; Ghelani, Nilesh B.; Shah, Sankit D.; Godhani, Chintan A.; Shah, Virank V. (International Journal of Research in Medical Sciences, 2025)
Background: Microvascular reconstruction is crucial in head and neck oncoplastic surgery following ablative procedures. However, prior surgery, radiation or tumor recurrence often leads to a vessel-depleted neck, making free flap transfer technically challenging. Methods: This prospective study included 30 patients undergoing microvascular reconstruction in a vessel-depleted neck over two years’ period. Preoperative imaging with doppler ultrasonography was performed for vessel mapping. Intraoperatively, meticulous dissection of ipsilateral vessels was attempted first. Free flaps used included anterolateral thigh, free fibula, and radial forearm, chosen for their long vascular pedicles. Results: All patients achieved successful flap survival, with no flap failures (100% survival). In all cases, ipsilateral vessels were usable despite prior surgery or radiotherapy. Contralateral dissection and vein grafting were not required in our series. End-to-side or end to end anastomosis to the internal jugular vein or its branches with corresponding arteries proved reliable. Prior radiotherapy did not adversely affect outcomes. Conclusions: Microvascular reconstruction in vessel-depleted necks is surgically demanding but feasible with careful planning, patience, and detailed anatomical knowledge. Meticulous dissection and use of flaps with long pedicles allow consistently high success rates, minimizing the need for vein grafts or contralateral vessel exploration.